TO COMPARE THE INCIDENCE OF POST DURAL PUNCTURE HEADACHE WITH PENCIL POINT 25 GAUGE WHITACRE VERSE CUTTING 25 GAUGE QUINCKE SPINAL NEEDLE IN PATIENTS FOR C SECTION UNDER SPINAL ANAESTHESIA - Adil Mehraj; Akram Raja; Shafqat Rehman; Noreen Adil (Pakistan Armed Forces Medical Journal, 2020)
Objective: To compare the incidence of post dural puncture headache with pencil point 25 gauge Whitacre verse cutting 25 gauge Quincke spinal needle in patients for C section under spinal anaesthesia.